Eculizumab in paroxysmal nocturnal haemoglobinuria and atypical haemolytic uraemic syndrome: 10‐year pharmacovigilance analysis. (15th February 2019) - Socié, Gérard; Caby‐Tosi, Marie‐Pierre; Marantz, Jing L.; Cole, Alexander; Bedrosian, Camille L.; Gasteyger, Christoph; Mujeebuddin, Arshad; Hillmen, Peter; Vande Walle, Johan; Haller, Hermann
Summary: Eculizumab is the first and only medication approved for paroxysmal nocturnal haemoglobinuria (PNH) and atypical haemolytic uraemic syndrome (aHUS) treatment. However, eculizumab safety based on long‐term pharmacovigilance is unknown. This analysis summarises safety data collected from spontaneous and solicited sources from 16 March 2007 through 1 October 2016. Cumulative exposure to eculizumab was 28 518 patient‐years (PY) (PNH, 21 016 PY; aHUS, 7502 PY). Seventy‐six cases of meningococcal infection were reported (0·25/100 PY), including eight fatal PNH cases (0·03/100 PY). Susceptibility to meningococcal infections remained the key risk in patients receiving eculizumab. The meningococcal infection rate decreased over time; related mortality remained steady. The most commonly reported serious nonmeningococcal infections were pneumonia (11·8%); bacteraemia, sepsis and septic shock (11·1%); urinary tract infection (4·1%); staphylococcal infection (2·6%); and viral infection (2·5%). There were 434 reported cases of eculizumab exposure in pregnant women; of 260 cases with known outcomes, 70% resulted in live births. Reporting rates for solid tumours (≈0·6/100 PY) and haematological malignancies (≈0·74/100 PY) remained stable over time. No new safety signals affecting the eculizumab benefit‐risk profile were identified. Continued awareness and implementation of risk mitigation protocols are essential to minimise risk of meningococcal and other Neisseria infections in patients receiving eculizumab. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.